Testing Times: The Social Life of Non-invasive Prenatal Testing. (March 2021) - Thomas, Gareth M.; Rothman, Barbara Katz; Strange, Heather; Latimer, Joanna E.
Non-invasive prenatal testing (NIPT) is a genomic technology used to predict the chance of a foetus having a genetic condition. Despite the immediacy of this technology's integration into clinical practice, there is a dearth of evidence outlining how both patients and professionals experience NIPT on the ground. In this article, we draw upon our collective empirical research—specifically on earlier screening technologies (BKR), Down syndrome screening (GT), genetic screening/testing (JL) and NIPT (HS)—to outline the most pressing and often controversial issues which, we argue, remain unresolved and vital to consider regarding NIPT. We begin with a brief introduction to NIPT as a prenatal technology and the bodies of literature which unpack its 'social life'. In what follows, BKR discusses NIPT within the context of her research on 'the tentative pregnancy' and diagnostic testing in the USA. In the following sections, GT, HS and JL identify different, but related, concerns with respect to NIPT, particularly around routinisation, commercialisation, choice, abortion, and configurations of disability and 'normalcy'.